An Investigation of Factors That Motivate Academics to Conduct Research and Research Productivity in Lao Public Universities - Sackdanouvong, Kertmee (Bumi Publikasi Nusantara, 2025)
This study is to investigate factors that motivate academics to conduct research and research productivity in Lao public universities. A quantitative research method was employed with a self-completed questionnaire was used and distributed to 336 academics in Lao universities, with valid and useable 301 forms were used for the data analysis, 89.58% response rate. The results indicated that recognition, respect, and job tenure were prominently perceived as the most influential extrinsic factors motivating academics to conduct research, whereas scholarly improvement, contributions, and interest were mostly perceived as the most influential intrinsic factors. The results also indicated that research support, culture, faculty size, and social network were perceived as the most contributing factors to academics’ research productivity. This study suggests that incentive policies and support for academics should be created at different levels based on the actual needs. Teachers’ teaching workload should be reduced for more time in conducting research. The universities should see the importance of creating a better research culture, establishing a rewarding mechanism at the faculty level, allocating more research funds, improving research facilities, as well as extending research collaboration with other universities in the country.